Elaboration and validation of a questionnaire assessing patient expectations about management of knee osteoarthritis by their physicians: the Knee Osteoarthritis Expectations Questionnaire. Issue 4 (6th May 2012) - Benhamou, Mathilde; Boutron, Isabelle; Dalichampt, Marie; Baron, Gabriel; Alami, Sophie; Rannou, François; Ravaud, Philippe; Poiraudeau, Serge
Abstract : Objectives: To develop a questionnaire assessing the expectations of patients regarding management of osteoarthritis (OA of the knee. Methods: A detailed document reporting on a qualitative analysis of interviews of patients with knee OA was sent to experts and a Delphi procedure was adopted for item generation. Eighty physicians (64 general practitioners, 16 rheumatologists) recruited 566 patients with knee OA to test the provisional questionnaire. Items were reduced according to their metric properties and exploratory factor analysis. The reliability of the questionnaire was tested by the Cronbach α coefficient. Construct validity was tested by divergent validity and confirmatory factor analysis. Test–retest reliability was assessed by the intraclass correlation coefficient (ICC) and the Bland–Altman technique. Results: Sixty items were extracted from analysis of the interview data. The experts needed three Delphi rounds to obtain consensus on a 33-item provisional questionnaire. The item reduction process resulted in an 18-item questionnaire. Exploratory factor analysis extracted three main factors: factor 1 represented expectations for education, factor 2 expectations for information on technical and human support, and factor 3 expectations for physician empathy. The Cronbach α coefficient was 0.91 (95% CI 0.89 to 0.92). Expected divergent validity was observed. Confirmation factor analyses confirmed higher intra-factor than inter-factor correlations. Test–retest reliability was good with an ICC of 0.79, and Bland–Altman analysis did not reveal a systematic trend. Conclusions: A new 18-item questionnaire assessing patient expectations of management of knee OA by their physicians is proposed. The questionnaire has good content and construct validity.